Assessment of tax subjects’ interaction under uncertainty of socio-economic processes - Kucherova, H.; Serhieieva, L.; Bilska, O.; Сергєєва, Людмила Нільсівна (My University, 2019)
Abstract. Topicality of research into interactions between tax environment subjects is justified by growing uncertainty of changes in socio-economic processes. The aim of this study is to assess interaction between taxpayers, controlling bodies and public authorities in view of dominant paradigms and results of expert and sociological research on subjects with regard to the degree of their influence on tax environment climate. Interaction is defined as a certain type of relations between subjects that result in developing mutual influence which induces corresponding changes of their states. Interaction is essentially a poorly structured category, which dictates a need to use soft modeling and subjective evaluation methods (matrix models). According to the degree of influence on tax environment climate, public authorities are proved to be the most influential subject, while taxpayers are found to be the least influential. Summative value of subjects’ interaction is set as Very Good. It is determined by taxpayers’ data as the best among other subjects. Based on the analysis of dynamics in parameters and activity of interaction subjects it is argued that in order to improve subjects’ interaction productivity, it is appropriate to improve the mechanisms of subjects’ interaction with public authorities of all others.